Foam and foam films : theory, experiment, application - Ekserova, D. R. (Dochi Ruseva) (Studies in interface science, 1998)
The main physicochemical aspects of foam and foam films such as preparation, structure, properties, are considered, giving a special emphasis on foam stability. It is shown that the foam and foam films are an efficient object in the study of various surface phenomena and in establishing regularities common for different interfaces, in particular, water/oil interface. The techniques and results on foam films have an independent meaning and involve the latest achievement in this field, with a focus on authors' results. The book has an expressed monographic character. It reveals joint ideas, i.e. the quantitative approach in treating foams is based on foam film behaviour and the techniques for controlling the foam liquid content, developed by the authors. A major contribution represents the independent consideration of formation and stability of foam films in theoretical and experimental aspects. No monograph published so far reveals these topics in the mentioned manner. Data and information about foams, physicochemical characterization of surfactants, phospholipids and polymers can also be found. Furthermore, the book provides information about: techniques involved in the study of foam films and foam structure and properties; foam drainage; processes of destruction in gravitational and centrifugal fields; reasons for stability of films and their role in the processes running in the foam; mechanical, rheological, optical, thermophysical, electrical properties; foam destruction upon addition of antifoams (mechanism of destruction, techniques, application); scientific principles of controlling foam properties and their application in foam separation and concentration; enhanced oil recovery; thermodynamic and non-equilibrium properties of foam films, stabilized by surfactants, phospholipids and polymers; techniques for the study of surface forces; formation and stability of foam films; black films, including bilayers; new theories of stability of amphiphile bilayer; experiments involved in this stability; application in biology and medicine.